PENGARUH RETURN ON ASSET, CURRENT RATIO, DEBT TO ASSET RATIO, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR PERTANIAN YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Astuti, Fuji; Dewi, Siska (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2024)
The Ministry of Finance had the worst financial results across all industrial and agricultural sectors in 2019. The lack of corporate assets is a factor. The purpose of this study is to find empirical evidence regarding the effect of return on assets (ROA), current ratio (CR), debt to asset ratio (DAR), and company size on financial distress. The population used is the agricultural sub-sector companies listed on the IDX as many as 23 companies with 5 years of observation. This study used a purposive sampling method. The analytical techniques used in this study are descriptive statistics, logistic regression analysis, hypothesis testing, and determinant testing. The results showed that return on assets (ROA) had no effect on financial distress. Current ratio (CR), and firm size had a negative effect on financial distress. Debt to asset ratio (DAR) had a positive effect on financial distress. Simultaneously return on assets (ROA), current ratio (CR), debt to asset ratio (DAR), and company size affect financial distress in agricultural sub-sector companies listed on the Indonesia Stock Exchange.